Strategic Cost Management (SCM) Analysis Based on Balanced Scorecard to Achieve Cost Leadership - Laiza Shendy Rindhyanti; Mutiara Damayanti; Ummi Kalsum Mutmainnah; Yusnaini Yusnaini (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
The escalation of global business dynamics in the VUCA era necessitates a shift from reactive cost management to an integrative Strategic Cost Management (SCM) approach. Conventional accounting is no longer sufficient to maintain competitive advantage amidst Industry 4.0 disruptions. This study critically analyzes the integration of a Balanced Scorecard (BSC)-based SCM architecture in constructing sustainable cost leadership without compromising long-term value creation. Employing a Systematic Literature Review (SLR) conforming to PRISMA 2020 guidelines, this research synthesized 31 peer-reviewed articles published between 2021 and 2026. The findings reveal that harmonizing SCM with the BSC framework reinforces cost leadership by aligning strategic cost drivers with multidimensional performance indicators.Instruments such as Activity-Based Costing (ABC) and Target Costing drive operational efficiency, while the BSC protects non-financial assets like service quality and human capital. Furthermore, current literature highlights a pivotal trend: the synergy of SCM and BSC is increasingly augmented by digital transformation and ESG metrics via the Environmental Sustainability Balanced Scorecard (ESBSC). Ultimately, success depends on an organization's technological maturity, governance quality, and adaptability to external environmental turbulence.